Sociodemographic, economic, physical, and mental health status of previously hospitalised patients with COVID-19 symptoms in Bangladesh: Protocol for a mixed-method study - Ahmed, Tanvir; Pooja, Shangjucta Das; Nandonik, Ahmed Jojan; Mostafa, Shamira; Kabir, Zarina Nahar (Frontiers in Public Health, 2023)
Introduction: There is not much is known about the long-term consequences of COVID-19, popularly known as Long COVID. This is particularly so in terms of patterns and clusters of symptoms over time, sociodemographic and economic profile of patients as well as their clinical history. This is crucial for resource constrained health systems of LMICs such as Bangladesh in order to address Long COVID as the forthcoming challenge. This protocol aims to investigate consequences of COVID-19 over time for physical and mental health and how these are associated with demographic and socio-economic factors. Methods and Analysis: This mixed-method study will collect information on all patients with symptoms of COVID-19 admitted to and discharged after recovery during the period April-December 2020 from a COVID-19 dedicated hospital in Bangladesh (N=942). Source of data will be admission records and discharge certificates from the hospital for clinical history, cross sectional survey on physical and mental health related symptoms and socioeconomic changes after recovery and qualitative in-depth interviews on experiences of COVID-19. Interviews will be conducted over phone. Quantitative data will use an electronic data collection platform and qualitative data, a flexible guideline. Quantitative analysis will be done to estimate prevalence of physical and mental health consequences of COVID-19 after recovery and changes in socio-economic status of the participants and to establish associations between the mental and physical health outcomes, and socio-economic and demographic information. The qualitative analysis will be performed using thematic analysis. Discussion: To devise strategies to address Long COVID, it is imperative to understand the post-COVID consequences and related health and non-health aspects to inform evidence-based policy making especially for resource-poor contexts such as Bangladesh. Given the dearth of evidence in this regard, the proposed study can contribute to bridging this knowledge gap. It is important to note that this study is one of the few which presents information on post COVID-19 consequences in the context of low- and middle-income country, and the first in Bangladesh.